Analysis of the Time Cost Trade-Off Method Application on Tug Boat 135 GT Repair Projects Owned by PT. Pelabuhan Indonesia II - Ari Wibawa Budi Santosa; Andi Trimulyono; Anugrah Firnandito; Joko Subekti; Eko Sasmito Hadi (Diponegoro University, 2024)
In the project implementation process, there is still the possibility of delays, as in the case of the Tanjung Buyut I Tug Boat ship repair project - 206 135 GT calculations are needed to accelerate the project to determine the optimum time and cost. One method that can be used in accelerating projects / crashing projects is the Time Cost Trade-Off method. This method can be used to solve this problem by adding specific alternatives such as working hours, labor, and other things with the minimum additional cost. In this study, an alternative acceleration was carried out by adding manpower and working hours duration of 1 to 4 hours which would be applied to the Hull repair project for the Tug Boat Tanjung Buyut I-206 135 GT. Based on the results of the analysis that has been carried out on the work of the Hull section, which is included in the critical activity, it is obtained that the most optimum duration acceleration is the addition of working hours (overtime) for 3 hours and an additional workforce of 24 peoples which results in an acceleration of time of 17 days from the normal duration of 60 days to 43 days with a time efficiency of 28%, as well as a cost reduction of IDR 19,700,000 or around 3.34% compared to the normal duration fee of IDR 571,950,000 to IDR 552,250,000.